A new and sustainable alternative food product: willingness to pay for cultured beef - Cinar, Gokhan; Bozkiran Yilmaz, Sidika (Frontiers in Sustainable Food Systems, 2025)
This study aimed to identify consumers in Türkiye's attitudes toward consuming cultured beef, a new and sustainable food product, their willingness to pay, and the factors influencing these consumption. A face-to-face survey was conducted with 386 individuals. In the study, the Critic method was used to determine the sensory factors in consumers' traditional beef consumption preferences, and the fuzzy paired comparison method was used to rank the priorities of the reasons for not consuming cultured meat. In addition, consumers' desire to consume cultured beef was determined by the conditional evaluation method, and the general price they wanted to purchase was determined by the lower bound mean method. Multidimensional scaling was used to create perception maps of consumers, and multiple correspondence analysis were used to determine consumption preferences according to demographic characteristics. A significant portion of participants were initially reluctant to consume cultured beef. The reluctant group had a higher tendency to fear consuming new foods (food neophobia) than the willing group. However, attitudes toward cultured beef consumption changed when different alternatives were presented and were positively influenced by the social environment, market availability, and price of the product. Consumers' willingness to pay for this product was $13.716/kg. At this price threshold, a significant portion of the population was willing to accept the product (29.27%). The consumer profile that wants to buy a product when its price drops is composed of male, middle-income and middle-aged people. Health concerns and taste expectations are the most significant sensory barriers to consumption motivation. The order of importance attributed to these factors varied by gender. The results of this study will guide the success of cultured meat, an alternative food product.